The characterization of elderly medication users living in long-term care facilities - Gautério, Daiane Porto; Santos, Silvana Sidney Costa; Pelzer, Marlene Teda; Barros, Edaiane Joana; Baumgarten, Larissa (Revista da Escola de Enfermagem da USP, 2012)
The objectives of this study were to characterize the elderly living in a long-term care facility in terms of their medication use and verify the existence of polypharmacy. This descriptive quantitative study was performed using a database from the research: The profile of the elderly living in a long-term care institution for the aged: a proposal for nursing/health action. A total of 39 elderly individuals who used medications were selected. It was found that most were women, aged between 80-89 years, who were literate and widowed. Circulatory system diseases were the most frequent. The elderly used a mean of 3.7 medications, and 30.8% took multiple medications. The most commonly used medications were for the cardiovascular system. It was found that some individuals used medications considered inappropriate for the elderly population. We hope to sensitize health professionals to promote a rational and careful use of medications among institutionalized elderly individuals.